A Critical Review of Protein Assays and Further Aspects of New Methods in BrewingScience - Steiner, Elisabeth; Back, Werner (BrewingScience, 2009)
Total nitrogen content of barley, malt and beer was usually measured by Kjeldahl method. In brewing science this method has been used for many years to measure total protein (N x 6.25 = protein concentration) in beer, but it measures nitrogen rather than proteins. Kjeldahl method determines total nitrogen but is prone to interference from non-protein and nitrogen-containing compounds, and fails to detect subtle changes in the protein content of wort and beer.Many quality attributes (e.g. turbidity, mouthfeel, foam stability) and processability (parameters such as filterability, are affected by the protein composition and content in beer. For example protein Z (MR 40 kDa) [12] is claimed to be responsible for haze formation and LTP1 [25] (MR 10 kDa) for foam stability. Siebert [23] suggests that a higher amount of proline results in a higher turbidity.Therefore, for brewers its is important to quantitatively measure the protein content and also to qualitative evaluate the protein composition in beer.The aim of this review is to describe and compare different methods of protein quantifi cation and qualifi cation. For that reason six different methods have been evaluated.